Benzimidazole design, synthesis, and docking to build selective carbonic anhydrase VA inhibitors. Issue 3 (1st February 2018) - Čapkauskaitė, Edita; Zakšauskas, Audrius; Ruibys, Virginijus; Linkuvienė, Vaida; Paketurytė, Vaida; Gedgaudas, Marius; Kairys, Visvaldas; Matulis, Daumantas
Graphical abstract: Abstract: The similarity of human carbonic anhydrase (CA) active sites makes it difficult to design selective inhibitors for one or several CA isoforms that are drug targets. Here we synthesize a series of compounds that are based on 5-[2-(benzimidazol-1-yl)acetyl]-2-chloro-benzenesulfonamide (1a ) which demonstrated picomolar binding affinity and significant selectivity for CA isoform five A (VA), and explain the structural influence of inhibitor functional groups to the binding affinity and selectivity. A series of chloro-substituted benzenesulfonamides bearing a heterocyclic tail, together with molecular docking, was used to build inhibitors that explore substituent influence on the binding affinity to the CA VA isoform.